Dekonstruksi syari'ah / Abdullahi Ahmed An-Na'im; penerjemah, Ahmad Suaedy, Amirudin Ar-Rany; editor, M. Jadul Maula, Imam Aziz - AN-NA'IM, ABDULLAHI AHMED; Ahmad Suaedy; Ar-Rany, Amirudin; M. Jadul Maula; M. Imam Aziz (Ircisod, 2016)
xxiii, 344 hlm. ; 21 cm.